Anticancer effects of 7,8-dihydromethysticin in human leukemia cells are mediated via cell-cycle dysregulation, inhibition of cell migration and invasion and targeting JAK/STAT pathway - Xiao Yi; Deng Taoran; Jiang Lijun; Wang Di (Acta Pharmaceutica)
The main focus of this research work was to study the anti-cancer properties of 7,8-dihydromethysticin against HL-60 leukemia cells. Investigations were also performed to check its impact on the phases of the cell cycle, cell migration and invasion, JAK/STAT signalling pathway and intracellular mitochondrial membrane potential (MMP) and reactive oxygen species (ROS). Cell proliferation was assessed through 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl tetrazolium bromide (MTT) assay and effects on colony formation were examined via clonogenic assay. Flow cytometry and Western blott analysis were performed to investigate the distribution of cell cycle phases. Flow cytometric analysis was performed for the examination of MMP and ROS production. The effect on JAK/STAT signalling pathway was examined through Western blot analysis. Results depicted that 7,8-dihydromethysticin induced concentration- as well as time-dependent inhibition of cell proliferation in leukemia HL-60 cells. Clonogenic assay indicated potential suppression in leukemia HL-60 cell colonies. The 7,8-dihydromethysticin molecule also caused cell cycle arrest at G2/M-phase along with concentration-dependent inhibition of cyclin B1, D1 and E. ROS and MMP measurements indicated significant ROS enhancement and MMP suppression with increasing 7,8-dihydromethysticin concentrations. Additionally, 7,8-dihydromethysticin led to remarkable dose-reliant inhibition of cell invasion as well as cell migration. Therefore, 7,8-dihydromethysticin should be considered a valuable candidate for leukemia research and chemoprevention.